2011
DOI: 10.3390/w3041128
|View full text |Cite
|
Sign up to set email alerts
|

Disinfection of Treated Wastewater and its Reuse in the Irrigation of Golf Grass: The Case of Plant M’zar Agadir-Morocco

Abstract: Abstract:The treated wastewater of Agadir M'zar plant has a good physico-chemical quality and it contains important nutrients (NPK: nitrogen, phosphorus, potassium). However, the reuse of this water, without disinfecting it, for irrigating the golf grass in the Agadir region, revealed the presence of a bacterial load that can hinder the quality and suitability of spaces for a population that is very demanding. Among the various methods of water disinfection, chlorination with bleach is the least expensive and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 9 publications
2
8
0
1
Order By: Relevance
“…In winter, the mean water temperature was 15 °C, ammonium and COD removals were 81% and 71% respectively. Results confirmed that this technique is performed as an advanced treatment system for COD and ammonium (Mouhanni, Bendou, & Er-raki, 2011;Arnal et al, 2008;Zhao et al, 2012). To determine the quality variation of the effluent from the M'zar plant during the seasons of the year 2006, the ratios are on Table 7.…”
Section: Removal Of Organic Pollutantssupporting
confidence: 61%
See 2 more Smart Citations
“…In winter, the mean water temperature was 15 °C, ammonium and COD removals were 81% and 71% respectively. Results confirmed that this technique is performed as an advanced treatment system for COD and ammonium (Mouhanni, Bendou, & Er-raki, 2011;Arnal et al, 2008;Zhao et al, 2012). To determine the quality variation of the effluent from the M'zar plant during the seasons of the year 2006, the ratios are on Table 7.…”
Section: Removal Of Organic Pollutantssupporting
confidence: 61%
“…Moreover, effluents from M'zar plant reflect an intense particulate pollution, especially during the summer, which is explained by a large hydraulic discharge following because of a huge industrial and domestic activity in the region. The industrial effluents are mainly generated by the food processing factories in the region (fish markets, canned meats and vegetables (Mouhanni, Hamdi, Bendou, Cavalli, & Benzine, 2012;Mouhanni, Bendou, & Er-Raki, 2011). The effluents from fish processing plants are loaded with large concentration of biodegradable organic matter, salts and also suspended solids.…”
Section: Physical Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…The average TSS/BOD 5 ratio is 0.51 ± 0.06 (Table 3), which is relatively low compared to the usual value (between 1.2 and 1.5) (Ministry of Land and of Morocco 2002). This report provides additional information about organic matter quantities in the effluent, but also provides information about sludge production (Mouhanni et al 2011).…”
Section: Tss/bod 5 Ratiomentioning
confidence: 99%
“…Sadly, just few studies have been carried out in Agadir (Mimouni et al 2002(Mimouni et al , 2003Alla et al 2006;Eddabra et al 2011), which is particularly characterized by an arid climate, and high industrial and agricultural activities. Many of the reported studies in Agadir were focalized on chemical risks (Mouhanni et al 2011;Aba-aaki et al 2013) and microbiological hazards of reuse of wastewater (Touyer et al 1998;Mimouni et al 2002Mimouni et al , 2003Eddaoudi et al 2004;Eddabra 2011;Fonteneau et al 2017). The purpose of this study is to evaluate the possibility of reusing treated wastewater from the Mzar treatment plant in the irrigation of green spaces.…”
Section: Introductionmentioning
confidence: 99%